Effect of Changing in Air Intake Temperature on Engine Performance Using Thermocouple - Nair Raman, Prem Kumar; Bahari, Azlina (Journal of Advanced Industrial Technology and Application, 2021)
This study will present the experimental result on the performance of spark ignition engine at various cooled air intake temperatures on four-stroke four-cylinder spark ignition engine. This study also investigated the level of emission released to the environment due to decrease in air intake temperature. In this study, the exhaust emissions percentage values of CO2 and HC are recorded by using Chassis Dynamometer (MD-2WD-500). The data was taken under three different gears (gear 2,3 and 4) at varying speed ( 1000,1500,2000,2500 and 3000 rpm) and intake temperature range (15â„ƒ~25â„ƒ). Based on the data and result recorded, decrease in temperature do increase the engine performance and also decrease the emission percentage as well